Perceived stress and psychological disorders in healthcare professionals: a multiple chain mediating model of effort-reward imbalance and resilience - Yuanling Tao; Zhen Cheng; Chenxi Wang; Ting Liu; Mi Yan; Xiaohong Huang; Shasha Jian; Li Sun; Zongtao Chen (Frontiers Media S.A., 2023)
BackgroundHealthcare professionals have shown more psychological disorders such as anxiety and depression due to the nature of work, which can cause job burnout, decrease the quality of medical services, and even endanger medical safety. The aim of the study is to explore the serial multiple mediating role of effort- reward imbalance and resilience between perceived stress and psychological disorders among healthcare professionals.MethodsA cross-sectional study was conducted in China from February to April 2023. A total of 2098 healthcare professionals at a tertiary general hospital was investigated by the following self-reported questionnaires: Hospital Anxiety and Depression Scale (HADS), Perceived Stress Scale (PSS), The Effort-Reward Imbalance (ERI), Healthcare professionals Resilience Scale (MSRS).ResultsAnxiety and depression are interrelated (r = 0.362, p < 0.01), and they were positively related to perceived stress (r = 0.640/0.607, p < 0.01) and ERI (r = 0.422/0.383, p < 0.01), and negatively related to resilience (r = −0.343/−0.320, p < 0.01). After controlling demographic factors, the variance in anxiety and depression was explained by perceived stress was 37.7 and 35.0%. Bootstrap analyses examining the pathway of perceived stress-ERI-resilience-anxiety revealed significant direct effects [B = 0.560, 95%CI (0.528, 0.591)], as well as indirect effects mediated independently by ERI [B = 0.045, 95%CI (0.029, 0.060)], resilience [B = 0.031, 95%CI (0.017, 0.047)], or a combination of both [B = 0.004, 95%CI (0.002, 0.007)]. Similarly, in the path of perceived stress-ERI-resilience-anxiety-depression, significant direct effects were found [B = -0.310, 95%CI(0.265, 0.351)], along with indirect effects mediated individually by ERI [B = 0.033, 95%CI(0.013, 0.052)], resilience [B = 0.014, 95%CI (0.001, 0.028)], and anxiety [B = 0.218, 95%CI (0.190, 0.246)], or by both or three together (B = 0.032).ConclusionThis study proved the hypothesis that ERI and resilience played a mediating role in perceived stress and psychological disorders, revealed the potential mechanism of anxiety in stress and depression, and proposed a solution for perceived stress to psychological distress, which can provide a basis for the intervention of healthcare professionals in the face of mental health crisis.